An evolutionary functional genomics approach identifies novel candidate regions involved in isoniazid resistance in Mycobacterium tuberculosis - Victoria Furió (Nature Portfolio, 2021)
Victoria Furió et al. apply functional genomics and evolutionary analyses to the study of antibiotic resistance in tuberculosis. Focusing on isoniazid resistance and using genomic data from clinical strains, they identify novel candidate genes with resistance mutations and further uncover the mechanisms underlying drug resistance.